Comorbidities in people living with HIV/AIDS and their impact on outpatient dental care - Maria Fernanda BARTHOLO; Jefferson Rocha TENÓRIO; Natália Silva ANDRADE; Cristiane Barbosa SILVEIRA; Karem López ORTEGA; Fabiana MARTINS; Marina GALLOTTINI (Brazilian Oral Research)
Abstract The objective of this study was to estimate the prevalence of comorbidities among people living with HIV/AIDS (PLWHIV) attending a dental outpatient clinic and discuss the impact of these comorbidities on dental management. A cross-sectional observational study evaluated 238 PLWHIV attending a specialized dental outpatient clinic in Brazil. We collected sociodemographic data, self-reported and physician-diagnosed comorbidities, hemogram results, CD4+ T cell count, viral load, use of combined antiretroviral therapy (cART), and information on harmful habits. The most prevalent comorbidities were sexually transmitted infections (STIs) (116/238; 48.7%), psychiatric disorders (105/238; 44.1%), and lipodystrophy (97/238; 40.8%). Men were more likely to have STIs (OR 4.0) and tuberculosis (OR: 2.5) (p < 0.05). Age ≥ 50 years increased the risk of diabetes mellitus by 2.6 times (p < 0.05). The risk of lipodystrophy (OR: 2.99, 95%CI 1.44–6.19) and psychiatric disorders (OR: 2.13, 95%CI 1.01–4.47) was greater in those who had been diagnosed with HIV for more than 20 years. In summary, psychiatric disorders and severe hematological alterations, such as anemia and neutropenia, are significant comorbidities that may limit dental treatment of HIV-positive patients. These findings underscore the need for integrated medical and dental care to address the complex health needs of PLWHIV.